Evaluation of Deficiency and Excessive Condition of Thrombin Burst Using Laboratory Tests - Wada, Hideo; Shiraki, Katsuya; Shimpo, Hideto; Miyata, Toshiyuki (Thrombosis and Haemostasis, 2025)
Thrombin burst is an important mechanism for hemostasis, which is enhancement and amplification of the coagulation cycle, especially activation of coagulation factors XI, VIII, and V by thrombin on the activated platelets. Thrombin burst monitoring has been performed using hemostatic molecular markers, thrombin generation test (TGT), thromboelastography (TEG), and clot waveform analysis (CWA). In particular, CWA is a routine laboratory test that is neither time consuming nor expensive. Arterial thromboses, such as acute myocardial thrombosis and acute cerebral thrombosis, are associated with excessive condition of thrombin burst, and clotting time using a small amount of thrombin in CWA can detect activated or procoagulant platelets. Thrombin burst deficiency is caused by abnormalities of platelets such as thrombocytopenia or clotting factors such as hemophilia and acquired clotting factor deficiency, showing different CWA patterns. Patients with clotting factor VIII inhibitors are treated with bypass therapy, such as recombinant activated clotting factor VII and activated prothrombin complex concentrate, which can be monitored by CWA, TEG, or TGT.
Keywords: clot waveform analysis; coagulation factor VIII; activated platelets; thrombin burst; bleeding diseases